URGENSI ANALISA 5C PADA PEMBERIAN KREDIT PERBANKAN UNTUK MEMINIMALISIR RESIKO - Ashofatul Lailiyah (Universitas Airlangga, 2014)
Application of the principle of 5 C in the banking world is often not implemented optimally by the banks. One factor is that the number of its targets to be achieved by the bank or the debtor is an urgent requirement so often do in any way to make the submission of credit is received by the bank. Principle 5 C should carry cumulatively, but in practice this principle applies only limited to whether the debtor has a large mortgage or not. It is actually going to bring impact on large-scale national development, especially economic development in Indonesia.Key words: principle 5C, banking, credit.